FILM DAN VIDEO TANPA MUSIK - Asharyanto, Muhammad; Anas, Afdal (Universitas Mercu Buana, 2023)
Films and videos are works of art that cannot be separated from music as an atmosphere builder to affect the emotions of the audience. So that many of the existing films and videos are built from music as the backing. However, aren't there any films or videos made without using music? By using a qualitative description method the author aims to collect data about films and videos that do not use music. The final results of this study found that there were several films and videos that were produced without using music. Like feature-length films, there is the films Turah. Short films or videos such as Top Soccer Shootout Ever With Scott Sterling (Original), Five Truths: Jerzy Grotowski, and Five Truths: Peter Brook.